High initial burst release of gentamicin formulated as PLGA microspheres implant for treating orthopaedic infection - Harun Ismail, Ahmad Fahmi; Doolaanea, Abd Monem; Awang, Mohamed; Mohamed, Farahidah (Academic Sciences, 2012)
Antibiotic treatment of orthopaedic infection is complicated by systemic toxicity and the need of effective therapeutic concentration necessary to ensure optimum killing of bacteria. To overcome the problem of systemic toxicity and to achieve a high initial release followed by sustained release of antibiotics, a new method of delivering gentamicin is attempted by encapsulating gentamicin into PLGA using multiple emulsion, solvent-evaporation method. Gentamicin was first extracted from the microspheres and quantified using ninhydrin assay before the concentration was measured using UV spectrophotometer. Gentamicin efficacy after encapsulation was preserved when CTAB (83.51 ± 1.42%) and low molecular weight (LMW) PLGA (82.38 ± 9.08%) were used as indicated by drug loading efficiency of more than 80% in the disc-diffusion assay. LMW PLGA enabled high burst release (~90%) of gentamicin within the first 10 hours corresponding to zone inhibition of 13.78 ± 0.86 mm, only 30% smaller than the positive control (10 mg/ml gentamicin). The effects of Tg Keywords: Micro particles, Gentamicin; Surfactant, PLGA, Controlled-release and molecular weight rather than surfactant types influence the initial burst release. The in vitro release profile suggests that by having a mixture of various PLGA microspheres in one dosage implant system, the high burst release can be sustained within therapeutic concentration for a prolonged period (> 1 months). This biodegradable delivery system does not entail another surgery to remove the implant hence reducing the high treatment cost usually associated with the non-biodegradable proprietary gentamicin-polymethyl-methacrylate (PMMA) beads currently in use.